A Constrained Choice? : Impact of Concessionality Requirements on Borrowing Behavior - Ahokpossi, Calixte (IMF Working Papers; Working Paper ;, 2014)
This paper uses the propensity matching score approach to assess the impact of the IMF's debt limits policy (DLP) on borrowing behavior in countries eligible to borrow from its concessional lending window. The paper finds that countries under the DLP borrow significantly higher amounts of concessional resources. However, there is no evidence that the DLP significantly impacts the level of non-concessional borrowing nor the terms of such borrowing. This result is confirmed by the heterogeneity analysis, suggesting that the level of development, rather than concessionality requirements, is the key driver of non-concessional borrowing.